Healthcare workers and COVID-19 pandemic: A fight amidst fear of burnout - Kanchan, Tanuj; Meshram, Vikas P; Singh Shekhawat, Raghvendra; Misra , Sanjeev (Journal of Indian Academy of Forensic Medicine, 2021)
COVID-19 pandemic is continuing to cause a huge impact on the wellbeing of the global population. The first case of COVID-19 in the world was reported in Wuhan, China in December 2019, and since then, it has spread worldwide. As the cases kept on increasing exponentially, the WHO declared COVID-19 as global pandemic on 11 March 2020. Fight against such health crisis required an exceptional response from the healthcare system and administrators. In India, it was always anticipated to be a daunting task to control the spread of infection due to a large and dense population and overburdened healthcare system. Healthcare workers, police personnel, defence personnel, sanitation workers, local administrators, etc., have been the frontline warriors in the fight against COVID-19 pandemic. Healthcare workers have been playing a pivotal role in the hospitals as well as community settings in management of the disease outbreak. In hospital set up, planning, preparedness and the optimal management of resources and manpower have been emphasized. The fight against COVID-19 pandemic has been long and continuing. In this long fight, physical and mental exhaustion leading to burnout among healthcare workers can be a major concern. Burnout can result from long term involvement in the work which is demanding and can lead to emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment. Multiple factors like fear of acquiring infection, lack of social support, discrimination and distancing behaviour from society, long working hours, inadequate work condition, inadequate 1 ,2 protective measures have been identified.